2018
DOI: 10.1148/radiol.2018171670
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Adenocarcinoma Staging in the Era of Preoperative Chemotherapy and Radiation Therapy

Abstract: Pancreatic ductal adenocarcinoma (PDA) remains among the most challenging malignancies to treat. At diagnosis, the tumor often already extends beyond the confines of the pancreas, spreading to an extent such that primary surgery with curative intent is very rarely feasible. Considerable momentum is now being given to a treatment strategy involving neoadjuvant chemotherapy or chemotherapy and radiation therapy in patients with nonmetastatic PDA. The main advantage of this strategy is better selection of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 99 publications
6
93
1
4
Order By: Relevance
“…2 Others reported that a combination of CTx and radiotherapy was the most significant positive prognostic factor for survival. 5,26,27 In this study, we had 4.3% perioperative mortality which is nearly similar to what was reported in other studies. 2,4,6,13,21,28 Seppänen et al, reported perioperative mortality 2.1%, and 5-year survival 22% after PD for PDAC.…”
Section: Discussionsupporting
confidence: 89%
“…2 Others reported that a combination of CTx and radiotherapy was the most significant positive prognostic factor for survival. 5,26,27 In this study, we had 4.3% perioperative mortality which is nearly similar to what was reported in other studies. 2,4,6,13,21,28 Seppänen et al, reported perioperative mortality 2.1%, and 5-year survival 22% after PD for PDAC.…”
Section: Discussionsupporting
confidence: 89%
“…CT is the modality of choice for the assessment of vascular invasion with a specificity of 82-100% and sensitivity of 70-96% [37][38][39][40]. Biphasic pancreatic CT, performed with thin slice thickness (< 3 mm, preferably 0.5-1 mm if available) and multi-planar reformatting, is the optimal technique to evaluate the peripancreatic arteries and veins during the pancreatic and portal venous phases, respectively [9].…”
Section: Evolving Imaging Criteria For Tumor Resectabilitymentioning
confidence: 99%
“…A borderline resectable (BR) tumor is an entity which fails to be classified under these two categories. This category is variable among different institutions particularly in defining the criteria related to venous invasion due to variations in vascular reconstruction surgeries [40]. In 2016, the International Association of Pancreatology (IAP) attempted to promote an international consensus to define borderline resectable PDAC (BR-PDAC) and included (1) anatomical, (2) biological, and (3) conditional criteria (Table 1) [50].…”
Section: Evolving Imaging Criteria For Tumor Resectabilitymentioning
confidence: 99%
“…The problem was identified clearly as early as 2001, with a study that suggested that CT after preoperative therapy seemed to underestimate the possibility of resecting a tumor to negative margins (29). The peculiar nature of the PDAC extensive and dense fibrous stroma, which after chemotherapy is often associated with a persistence of fibrosis tissue that prevents the tumor from shrinking on imaging-even after the destruction of cancer cells-seems to be the main responsible for this perceived lack of accuracy (30).…”
Section: Radiographic Responsementioning
confidence: 99%